Local Traditions in the Lens of Sharia: A Study of Manjua Julo-Julo - Yuliana, Fitria; Iska, Syukri; Rizal, Deri (Institut Agama Islam Negeri Batusangkar, 2024)
This study explores the practice of manjua julo-julo and provides an Islamic legal analysis of its implementation in Nagari Sungai Jambu, Pariangan District, Tanah Datar Regency. Employing a qualitative descriptive approach within field research, the primary data sources include four individuals directly involved in manjua julo-julo, while secondary data comes from three community leaders. The findings reveal that the manjua julo-julo practice within the community is categorized into two forms: first, julo-julo (labor exchanged for labor), and second, manjua julo-julo (labor exchanged for labor with the involvement of a third party). Prior to initiating agricultural cooperation, a mutual promise (wa'ad) is made among the farmer members involved in julo-julo and manjua julo-julo. These agreements utilize ijarah and shirkah contracts, specifically classified under syirkah abdan and ijarah. The practice of manjua julo-julo aligns with the principles of cooperation (syirkah) as it falls under shirkah abdan and meets the criteria for joint efforts, involving collaboration between rice field owners and workers. Furthermore, the implementation adheres to sharia principles, ensuring compliance with Islamic legal guidelines.